Trends and Issues in Educational Psychology - James S. Taylor; Larry D. Pound; Robert C. Newhouse (Educational Considerations, 1975)
The review of issues in educational psychology looks at areas of innovation as well as areas of stagnation. The authors challenge researchers to find meaningful information which has utility in the development and improvement of teaching.